Penetrating cardiac trauma: Analysis of 240 cases from a hospital in Bogota, Colombia (2017)
Background: Trauma characteristics and its management is influenced by socioeconomic context. Cardiac trauma constitutes a challenge for surgeons, and outcomes depend on multiple factors including initial care, characteristics of the wounds, and surgical management. Methods: This is a retrospective cross-sectional case series of patients with penetrating cardiac injuries (PCI) from January 1999 to October 2009 who underwent surgery in a trauma referral center in Bogotá, Colombia. Demographic variables, trauma characteristics, treatment, and outcomes were analyzed. Results: The study included 240 cases: 96.2% males, mean age of 27.8 years. Overall mortality was 14.6%: 11.7% from stab wounds and 41.2% from gunshot wounds. Upon admission, 44% had a normal hemodynamic status and 67% had cardiac tamponade. About 32% had Grade II injuries and 29% Grade IV injuries. In 85% of the cases, there were ventricular compromise and 55% of patients had associated lesions. In 150 cases, a pericardial window was performed. Highest mortality occurred in wounds to the right atrium. In tamponade patients, mortality was 20% being higher for gunshot wounds (54.5%) than for stab wounds (18%) (p = 0.0120). Conclusions: The study evidenced predominance of stab wounds. Based on characteristics of the trauma, patients, and survival rate, there is most likely a high pre-hospitalization mortality rate. The difference in mortality due to stab wounds and those produced by gunshots was more related to technical difficulties of the surgical repair than with the type of injury established by the Injury Grading Scale. Mortality was higher in patients with cardiac tamponade. Surgical management was satisfactory using pericardial window as the diagnostic method and sternotomy as the surgical approach. © 2017 The Author(s).